SECOND HAND CAR PURCHASING PROBLEM VIA AN INTEGRATED MULTI-CRITERIA DECISION MAKING SOFTWARE - Canpolat, Onur; Canpolat, Kadriye; Demir, Halil Ibrahim (MATTER: International Journal of Science and Technology, 2017)
Automotive industry shows a growing trend in recent years. Both new car and used car market is one of the leading sectors in many countries. In recent years, people prefer to purchase used or second-hand cars rather than new cars. Therefore, it is important to make right decision while purchasing second hand car. Consequently, second hand car purchasing problem (SHCPP) is an up-to-date multi criteria decision problem (MCDMP) almost throughout the world. A software is developed by using C# programming language and this software is usedto solve SHCPP problem. By using Entropy or Fuzzy Analytic Hierarchy Process (FAHP) methods weights of criteria of MCDM problems are calculated by using the developed software. Later this software can be used to determine the optimum alternative using Multi-Attribute Utility Theory (MAUT) or Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) which can be selected by user. Software has the flexibility to solve many different problems and has the diversity to select both methods of calculating weights of criteria and solution methods by user.